Languages of the World : Arabic - Daniel Nunn (China Raintree Publisher, 2013)
This series examines where in the world each language is spoken, who speaks it, differences and similarities between the language and English, and interesting facts about the language, including how it is used in everyday contexts such as meeting people, homes, schools, family, and food.
Keywords: Easy Read Nonfiction -- Easy Read Nonfiction